Safe effective triple therapy of infantile hemangioma using oral Propranolol and oral prednisolone plus topical timolol drops in series of 182 infants. - Sharquie, Khalifa E.; Jabbar, Raed I. (Journal of Pakistan Association of Dermatologists, 2023)
Background Infantile hemangioma is a common vascular tumor that involute gradually as part of natural course but in many cases it needs active treatment especially when they are located adjacent to a vital organ or huge in size by using oral propranolol or other alternative measure. Objective To record personal experience in treating infantile hemangioma using triple therapy on home basis. Patients and Methods This is a case series cross sectional clinical study and therapeutic trial of infantile hemangioma(IH) was carried out during the period from 2014-2022 where all cases with infantile hemangioma were evaluated. All types of hemangioma were included single or multiple superficial and deep. Oral propranolol was given at home in a dose of 1-2 mg/kg body weight a day in two divided doses. Oral prednisolone was started as 5mg syrup once a day for one month and then tapered gradually. Also timolol drop 0.5% was applied to hemangioma twice a day till the end of therapy. The duration of treatment ranged from 3-6 months with a median of 4 months. Objective scoring was used to assess the response to therapy. All side effects were carefully recorded by the mothers and dermatologist. Results A total of 182 infants,129(70.87%) females and 53 (29.12%) males with IHs were included and analyzed. The age of the patients ranged from 1-6 months with a mean of 4 months. The sites of lesions were mostly on heads including face and neck in 106(58.24%) cases while in other parts of body in 76(41.75%) cases, with size ranged from 2 cm2 to 23 cm2. The response to triple therapy was noticed week after starting treatment protocol but was obvious at 2 weeks. There was gradual reduction in color and size of lesions. In most of patients, there was about 25% reduction in the first two weeks that reached to 75-100% after 3-6 months. No adverse or side effects were seen in all infants even with normal growth development. Conclusion This triple therapy is the first study using oral propranolol and oral prednisolone plus topical timolol drops together on a home basis. It is safe effective therapy for infantile hemangioma and is more effective than single drug use. No need for hospital admission or cardiac assessment during treatment course and no laser therapy is recommended.